The defects of lace-up surgical masks and related solutions in operating rooms. (September 2021) - Wang, X.; Lin, F.; Wang, Z.; Hu, J.; Li, X.; Zhu, B.; Zhang, J.
Summary: Background: It is difficult to make a lace-up surgical mask fit tightly to the face with conventional wearing methods because of the strings' poor tension, resulting in some air flowing through the gap. We introduced two feasible new wearing methods and obtained satisfactory experimental results. Methods: The wearing of surgical masks by staff was investigated through observation and interview in operation rooms. The required time to don, close-fitting rates, and satisfaction of the conventional method and the two new recommended methods were counted and compared, according to the subjects' experience. The differences between the three wearing methods on the microbial contamination of the sterile area were explored in a mock operation. Results: In the subjects' experience, the close-fitting rates were 47.0%, 92.0% and 100.0% in the conventional, Three Knots, and Elastic Band groups, respectively ( P <0.001); the satisfaction scores evaluated by numerical rating scale from 0 to 10 were 5.06 ± 2.22, 6.89 ± 1.86 and 7.10 ± 1.72, respectively ( P <0.001); the required times were 14.32 ± 2.20, 25.76 ± 5.13 and 27.37 ± 5.11 s, respectively ( P <0.001). In the mock operation, there were significant differences between the conventional and Three Knots groups (37.5 (13) vs 18 (8) cfu, P <0.001), as well as between the conventional and Elastic Band groups (37.5 (13) vs 17(10) cfu, P <0.001). Conclusions: The recommended new wearing methods had the advantages of closer fit, higher satisfaction rates, were more comfortable, and resulted in lower contamination of the sterile area; however, the recommended two methods required more time.